Sustained Flow: Affective Obsession in Second Language Learning - Ibrahim, Zana (Frontiers in Psychology, 2020)
A Directed Motivational Current (DMC) or sustained flow (SF; Ibrahim & Al-Hoorie, 2019) is a motivational phenomenon characterized by intensity of engagement and sustainability of effort in which individuals display highly motivated goal-governed behaviour and achieve outcomes exceeding expectations set at the outset (Dörnyei et al., 2015; Dörnyei et al., 2014). This paper presents an empirical investigation into what fuels the intense and sustained motivated behavior which distinguishes the phenomenon from other types of high motivated engagement such as the ones maintained by volitional, self-regulatory measures. The qualitative (phenomenological) analysis of interview data collected from a number of subjects who had experienced sustained flow reports two main findings. First, high motivation and intense engagement in sustained flow are primarily the function of affective obsession with the SF experience. Once in SF, people will be mentally and affectively consumed by their experiences even at times when they are involved in other daily activities. Second, as a result of one’s affective appraisal of SF experience, one’s perception toward effort will change from viewing learning tasks as homework to perceiving engagement as one’s preferred activity conducted at one’s free times. In SF, engagement is probably considered as too emotionally satisfying and meaningful insomuch as one prefers to maintain a strong and constant sense of relatedness. As a result, effort loses its traditional connotation and therefore self-regulatory measures become unnecessary; hereby one might invest the maximum amount of effort toward learning. Theoretical implications of these two main findings are then discussed in relation to the motivational power of positive affect in directing second language learning behavior.